STATUS HUKUM BARISAN REVOLUSI NASIONAL DALAM KONFLIK BERSENJATA DI THAILAND SELATAN - Winna Ellianne; Jun Justinar (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2021)
This paper aims to discuss the actions related to humanitarian law by the Thai Government inovercoming armed conflicts that occur in the country with the emergence of an organized armedgroup, namely the National Revolutionary Front or BRN for short. Knowing that the rebel groupsare Muslim majority and domiciled in the Southern Thailand area there is a conflict with the ThaiGovernment and the motivation to release the Southern Thailand province from the Thaigovernment to form an Islamic state. Armed disputes that began in 2004 with several armedconfrontations that pose a danger to civilians and threaten the security and defense of thecountry which then urged the Thai Government to increase defense and military strength in thearea concerned in suspending the BRN. Because armed conflict occurs within the sovereignterritory of the Thai state, this conflict is a non-international armed conflict that is also motivatedby an organized armed group's goal to gain independence and secede from its main state. Thehistory of the collapse of the Patani Kingdom in Southern Thailand is the main reason for theconflict that occurred in this case.